Possession, Feelings of Ownership, and the Endowment Effect - REB, Jochen (Institutional Knowledge at Singapore Management University, 2007)
Research in judgment and decision making generally ignores the distinction between factual and subjective feelings of ownership, tacitly assuming that the two correspond closely. The present research suggests that this assumption might be usefully reexamined. In two experiments on the endowment effect we examine the role of subjective ownership by independently manipulating factual ownership (i.e., what participants were told about ownership) and physical possession of an object. This allowed us to disentangle the effects of these two factors, which are typically confounded. We found a significant effect of possession, but not of factual ownership, on monetary valuation of the object. Moreover, this effect was mediated by participants' feelings of ownership, which were enhanced by the physical possession of the object. Thus, the endowment effect did not rely on factual ownership per se but was the result of subjective feelings of ownership induced by possession of the object. It is these feelings of ownership that appeared to lead individuals to include the object into their endowment and to shift their reference point accordingly. Potential implications and directions for future research are discussed.